A Rev-Independent Human Immunodeficiency Virus Type 1 (HIV-1)-Based Vector That Exploits a Codon-Optimized HIV-1 gag-pol Gene - Kotsopoulou, Ekaterini (American Society for Microbiology, 2000)
The human immunodeficiency virus (HIV) genome is AU rich, and this imparts a codon bias that is quite different from the one used by human genes. The codon usage is particularly marked for the gag, pol, and env genes. Interestingly, the expression of these genes is dependent on the presence of the Rev/Rev-responsive element (RRE) regulatory system, even in contexts other than the HIV genome. The Rev dependency has been explained in part by the presence of RNA instability sequences residing in these coding regions. The requirement for Rev also places a limitation on the development of HIV-based vectors, because of the requirement to provide an accessory factor. We have now synthesized a complete codon-optimized HIV-1 gag-pol gene. We show that expression levels are high and that expression is Rev independent. This effect is due to an increase in the amount of gag-pol mRNA. Provision of the RRE in cis did not lower protein or RNA levels or stimulate a Rev response. Furthermore we have used this synthetic gag-pol gene to produce HIV vectors that now lack all of the accessory proteins. These vectors should now be safer than murine leukemia virus-based vectors.